Gastroesophageal reflux disease as a factor associated with bronchial asthma in the pediatric population: Enfermedad por reflujo gastroesofágico como factor asociado a asma bronquial en población pediátrica - Ricra, Rafael (2020)
Objective: To determine the relationship between gastroesophageal reflux disease and bronchial asthma in the pediatric population of the National Children's Hospital Breña headquarters between the years 2017-2018. Methods: An analytical observational study of cases and controls was not matched, with a ratio of 1 case to 2 controls, with a total of 45 cases and 90 controls, a simple random probability sampling was performed, with a retrospective collection for the variables bronchial asthma, GERD, GERDinduced esophagitis, prematurity, interrupted breastfeeding, sex and age. A bivariate and multiple logistic regression model was performed to obtain the Odds Ratio for the strength of association. Results: A statistically significant difference was found for GERD (p = 0.002), being 33.33% and 11.11% for cases and controls, as well as for interrupted lactation (p = 0.013); by multiple logistic regression analysis the variables GERD (OR 4.27, p = 0.003, CI 1.64-10.92) and interrupted breastfeeding (OR 2.74, P = 0.011, CI 1.26-5.97 ) presented a relationship for bronchial asthma. Conclusion: A relationship was found between GERD and bronchial asthma which can be extrapolated to the pediatric population of the city of Lima, this is the first article published in this regard at the national level, prospective studies are recommended to determine causality.